Annual Abstract of Statistics 1985 - Nigeria. Federal Office of Statistics (Lagos : Federal Office of Statistics, 1985)
1985 edition of the annual abstract of statistics prepared by the Federal Office of Statistics, Lagos.
lje 15/3/2019
Loans
Keywords: Statistics; Annual Report